PEMBELAJARAN BAHASA INDONESIA BERDASARKAN PENDEKATAN SAINTIFIK (PROBLEM BASED LEARNING) BERFALSAFAH TRI HITA KARANA DI KELAS VII SMP NEGERI 2 SINGARAJA - I Gusti Agung Made Gede Mudana (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
This research aims to describe (1) lesson plan, the application, and the evaluation of Indonesian learning based on scientific approach philosophy of Tri Hita Karana in class VII SMP Negeri 2 Singaraja. This research is using descriptive qualitative method. The data in this research is compiled using documentation method and observation method. The data is analyzed which are the data reduction, data classification, and the drawing of the conclusion. The subject in this research is the Indonesian teacher in class VII SMP Negeri 2 Singaraja. The result of the study shows that (1) in lesson planning, five main activities in scientific approach philosophy of Tri Hita Karana are planned on the lesson plan steps component. (2) In the implementation of learning activity, five main activities in scientific approach philosophy of Tri Hita Karana appear in the learning activity and it implemented in two meetings. (3) In the assessment, it covers assessment of knowledge and skill aspects. According to that result, educational institution are suggested to use this research as the theory providers according to scientific approach philosophy of Tri Hita Karana in language learning. The teachers are suggested for more careful in setting the lesson plan. The other researchers are suggested to continue in conducting the study about the implementation of scientific approach philosophy of Tri Hita Karana in learning. Keywords: Indonesian learning, scientific approach, Tri Hita Karana